Does the unemployment rate moderate the well-being disadvantage of the unemployed? Within-region estimates from the European Social Survey - Gábor Hajdu; Tamás Hajdu (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
Using eight waves of the European Social Survey, we analysed how the local unemployment rate influences the well-being disadvantages of the unemployed. We estimate region fixed effects and slopes models that, unlike the standard region fixed effects approach, provide an unbiased estimate of the cross-level interaction term (the term between being unemployed and the unemployment rate). We find that the satisfaction of unemployed people (relative to employed people) is lower when the unemployment rate is higher. The results are similar for the depression scores, but the differences are smaller and insignificant regarding the happiness scores. Our results do not support the 'social norm of unemployment' hypothesis that states that the negative impacts of unemployment are smaller if the unemployment rate is higher. In contrast, these results are in line with the argument that worse re-employment perspectives in high-unemployment regions may be particularly harmful to unemployed people. We note that these results do not contradict the claim that, in regions with a weaker social norm to work, unemployed people may be more satisfied. Instead, the results suggest that the unemployment rate is not a good proxy for the social norm to work
Keywords: I31; J64; 330; unemployment; subjective well-being; unemployment rate; life satisfaction; happiness; European Social Survey; ESS